Proceedings of the 25th International Conference on Machine Learning - ICML '08 2008
DOI: 10.1145/1390156.1390197
|View full text |Cite
|
Sign up to set email alerts
|

Optimized cutting plane algorithm for support vector machines

Abstract: We have developed a new Linear Support Vector Machine (SVM) training algorithm called OCAS. Its computational effort scales linearly with the sample size. In an extensive empirical evaluation OCAS significantly outperforms current state of the art SVM solvers, like SVM light , SVM perf and BMRM, achieving speedups of over 1,000 on some datasets over SVM light and 20 over SVM perf , while obtaining the same precise Support Vector solution. OCAS even in the early optimization steps shows often faster convergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 12 publications
1
118
0
Order By: Relevance
“…b) Support Vector Machine (SVM) using kernel function with linear mapping [33], which is composed with the m 1 (x) and a randomly chosen subset from the trained data. It is trained using a fast cutting plane algorithm [35].…”
Section: Voxel Classificationmentioning
confidence: 99%
“…b) Support Vector Machine (SVM) using kernel function with linear mapping [33], which is composed with the m 1 (x) and a randomly chosen subset from the trained data. It is trained using a fast cutting plane algorithm [35].…”
Section: Voxel Classificationmentioning
confidence: 99%
“…Such landmark positions are used for normalized face image construction, which is used in the next recognition step. The problem of gender and identity estimation are classification problems, for which we use multi-class Support Vector Machine (SVM) classifier, more precisely the implementation done by Franc [10]. The classifier uses image features, computed from normalized face images, based on Local Binary Patterns (LBP).…”
Section: Face Recognitionmentioning
confidence: 99%
“…The modified algorithm is called the optimized cutting plane algorithm (OCAS) [48], and it was shown that the number of iterations needed for convergence is the same order as that in [47]. On the other hand, OCAS is reported to be much faster in numerical experiments than the algorithm proposed in [47].…”
Section: ) the Empirical Risk Is Expressed Asmentioning
confidence: 99%